2015
DOI: 10.3389/fpsyg.2015.01392
|View full text |Cite
|
Sign up to set email alerts
|

The power of putting a label on it: green labels weigh heavier than contradicting product information for consumers’ purchase decisions and post-purchase behavior

Abstract: Green products are appealing. Thus, labeling products as environmentally friendly is an effective strategy to increase sales. However, the labels often promise more than the products can actually deliver. In the present research, we examined the expectation that consumers with high ecological motivation have strong preferences for green-labeled products – even when presented product information contradicts the label’s image. This unsettling hypothesis is grounded in the labels’ potential to create a cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 58 publications
5
40
2
1
Order By: Relevance
“…Notably, the results reveal how strong the information provided by the brand may be to (materialistic) consumers, as the brands were randomly presented with the products, ensuring that the products displayed with the luxury brand would be preferred, even when the information conveyed by the brand was not congruent with the product's quality. This specific result, being consistent with previous research (e.g., Hahnel et al, 2015), highlights that values are important factors that have to be taken into account when studying consumer decision-making.…”
Section: Materialists Mean (Sd)supporting
confidence: 92%
“…Notably, the results reveal how strong the information provided by the brand may be to (materialistic) consumers, as the brands were randomly presented with the products, ensuring that the products displayed with the luxury brand would be preferred, even when the information conveyed by the brand was not congruent with the product's quality. This specific result, being consistent with previous research (e.g., Hahnel et al, 2015), highlights that values are important factors that have to be taken into account when studying consumer decision-making.…”
Section: Materialists Mean (Sd)supporting
confidence: 92%
“…Hence, within the scale developed in this research, awareness and involvement are integrated in a single dimension, which is also validated empirically by Principal and that eco-labels influence buying decisions (Thøgersen, 2000). Engel, Blackwell, and Miniard (1995)'s classic model of consumer involvement categorizes consumers as having either high or low level of involvement, and researchers have found consumers' involvement influences their engagement with environmental information (Hahnel et al, 2015). High involvement consumers would be more receptive to eco-labelling.…”
Section: Consumer Awareness and Involvementmentioning
confidence: 82%
“…Engel, Blackwell, and Miniard ()’s classic model of consumer involvement categorizes consumers as having either high or low level of involvement, and researchers have found consumers’ involvement influences their engagement with environmental information (Hahnel et al, ). High involvement consumers would be more receptive to eco‐labelling.…”
Section: Literature Review and Dimensions Of Eco‐label Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown interactions between environmental values and behavior in other domains than performance. For example, people higher in environmental concern showed stronger preference for eco-friendly products, in particular, stronger purchase intentions and taste preferences (Hahnel et al, 2015;Sörqvist et al, 2013).…”
Section: Mechanisms Underpinning Behavioral Change By Eco-labelingmentioning
confidence: 99%